Perkembangan Studi Hadis di Barat Sebuah Studi Perbandingan Antara Masa Lalu dan Masa Kini: PERKEMBANGAN STUDI HADIS DI BARAT: Studi Perbandingan Antara Masa Lalu dan Masa Kini - Haq, Syamsul (Jurnal Studi Islam dan Sosial, 2024)
The development of relations between the West and the Islamic world in recent decades has increased the interest of Western scholars in the study of Islam in general, especially the interest in a single subject, the Hadith. Some renowned western scholars in the past took considerable interest in hadith studies with the critical method approach in assessing the authenticity of hadith such as Ignaz Goldziher, Joseph Schacht, and G.H.A Juynboll. More recently, contemporary hadith studies are more famous for the interdisciplinary approach that combines various disciplines to determine the authenticity and falsity of hadith, such as those of Harald Motzki and Jonathan A.C. Brown. This study aims to analyze the development of hadith studies in the western world by conducting a comparative time study approach between the past and the present. This research uses descriptive qualitative methods and literature studies as additional references. Data collection is used library research from leading journal articles, books, and information from the internet as secondary sources. The results of this study show that the development of hadith in the West between past (19th Century) and present (21st Century) has significantly transformed from a critical approach that is skeptical of the authority of Islamic traditions in the past by Ignaz Goldziher and Joseph Schacht, to a more inclusive interdisciplinary approach with the History Critical Method towards biblical studies. Furthermore, the results show that the development of hadith studies by Western scholars between past and present is intended to enhance our understanding of the history, methodology, content and relevance of hadith with variations of change over time.